Humour in experiential marketing campaigns and its perception by Czech university students - Navrátilová, Ludmila; Milichovský, František (Mendel University in Brno, 2015)
At present, it is necessary to monitor marketing communication strategy connected to actual customers’ needs and requirements. At the same time, there is important to respect gender of customers. The paper provides an overview of current marketing communication trends of the companies. Based on the theoretical data there are applied statistical methods, which should be achieved of main aim of the paper. The main aim of the paper is to find connections between communication and gender from point of view of humour. To support this approach theoretical information from the area of marketing communication connected with data from primary research were used. Success companies know customers’ needs for long-term strategic development of relationship marketing with customers. That is necessary to reach the customers’ emotion and their irrationality of purchase decision. For this contact companies try to use experiential marketing full of humour elements as the way to increase own turnover. Adequate communication campaigns could create acceptable background for effective marketing. The article is focused on dependency between genders and used marketing communication tools. The objective of this research is to verify intensity dependence of marketing communication in connection with respondents´ gender and to identify impacts of the marketing communication and to describe communication trend. The research was aimed in random chosen group of young people in the Czech Republic. It was made data processing by statistical software IBM SPSS Statistics 20 to obtain relevant answers.

At present, it is necessary to monitor marketing communication strategy connected to actual customers’ needs and requirements. At the same time, there is important to respect gender of customers. The paper provides an overview of current marketing communication trends of the companies. Based on the theoretical data there are applied statistical methods, which should be achieved of main aim of the paper. The main aim of the paper is to find connections between communication and gender from point of view of humour. To support this approach theoretical information from the area of marketing communication connected with data from primary research were used. Success companies know customers’ needs for long-term strategic development of relationship marketing with customers. That is necessary to reach the customers’ emotion and their irrationality of purchase decision. For this contact companies try to use experiential marketing full of humour elements as the way to increase own turnover. Adequate communication campaigns could create acceptable background for effective marketing. The article is focused on dependency between genders and used marketing communication tools. The objective of this research is to verify intensity dependence of marketing communication in connection with respondents´ gender and to identify impacts of the marketing communication and to describe communication trend. The research was aimed in random chosen group of young people in the Czech Republic. It was made data processing by statistical software IBM SPSS Statistics 20 to obtain relevant answers.
Humour in experiential marketing campaigns and its perception by Czech university students
Keywords: marketing communication; new trends; experiential marketing; humour; marketing communication; new trends; experiential marketing; humour